Genome-wide identification of UDP-glycosyltransferases in the tea plant (Camellia sinensis) and their biochemical and physiological functions - Hoffmann, Timothy D.; Kurze, Elisabeth; Liao, Jieren; Hoffmann, Thomas; Song, Chuankui; Schwab, Wilfried (Frontiers in Plant Science, 2023)
Tea (Camellia sinensis) has been an immensely important commercially grown crop for decades. This is due to the presence of essential nutrients and plant secondary metabolites that exhibit beneficial health effects. UDP-glycosyltransferases (UGTs) play an important role in the diversity of such secondary metabolites by catalysing the transfer of an activated sugar donor to acceptor molecules, and thereby creating a huge variety of glycoconjugates. Only in recent years, thanks to the sequencing of the tea plant genome, have there been increased efforts to characterise the UGTs in C. sinensis to gain an understanding of their physiological role and biotechnological potential. Based on the conserved plant secondary product glycosyltransferase (PSPG) motive and the catalytically active histidine in the active site, UGTs of family 1 in C. sinensis are identified here, and shown to cluster into 21 groups in a phylogenetic tree. Building on this, our current understanding of recently characterised C. sinensis UGTs (CsUGTs) is highlighted and a discussion on future perspectives made.